DEVICE FOR TESTING RECEIVERS - IVLIEV, ANTON; KORNIEV, VOLODYMYR; BONDARENKO, VIKTOR; BONDARENKO, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Due to the current situation in the country, the issue of availability of devices for testing receivers is becoming urgent. In general, receivers operate at high frequencies up to 8GHz, so testing will be done using a sine wave generator that should generate a frequency between 62.5 MHz and 8 GHz. Market analysis shows that such generators mainly exist for laboratory conditions, are quite expensive and bulky. This article is devoted to the development of a compact device of high quality, designed for the generation of high-frequency signals, operating in field conditions and cheaper than similar devices. The best solution for generating high-frequency signals is a compact voltage-controlled generator (VCG) implemented on ready-made microcircuits. VCG works on the principle of an oscillating LC circuit, in which the frequency can be set by changing the capacitor capacity or the coil inductance. In parallel with the capacitor, a varicap is connected - a capacitor of variable capacity, which is controlled by voltage. VCGs are quite unstable and can change their frequency depending on various factors, for example: temperature, pressure, humidity. Therefore, a PLL (Phase Locked Loop) system is connected to the generator, as a microcircuit with a built-in PLL. Such microcircuits are usually programmed using the SPI serial protocol. The different receivers to be tested by the designed device have different sensitivities, so an attenuator is added before the high-frequency output, which should be variable and suppress the signal from 0 to 31.5 dBm. To control the PLL and the attenuator, a reliable and widely used STM32 microcontroller, which has the necessary functionality, is chosen. The microstrip line was simulated in the CST Studio software environment for a given frequency. In the future, it is expected to improve the device in the part of controlling the generation of high-frequency pulses using switches and improving the software for controlling the generator.
Keywords: voltage-controlled generator (VCG); microstrip line; PLL; attenuator; STM32 microcontroller; CST Studio